A multi-class decentralised event-triggered control framework for congestion and emission reduction in freeway networks. Issue 9 (2018) - Pasquale, C.; Sacone, S.; Siri, S.; Ferrara, A.
Abstract: The present work deals with the problem of regulating traffic in freeway networks via ramp metering with the twofold objective of reducing congestion and traffic emissions. In this paper, an answer to this problem is given by proposing a multi-class decentralised control scheme that acts according to an event-triggered logic. Local control algorithms receive local measurements from the freeway network and make a periodic prediction on the local system evolution. On the basis of this information, the local control algorithms communicate suitable parameters to the local feedback controllers, which produce control actions able to jointly reduce the congestion and the traffic emissions in a neighbourhood of the controlled on-ramp. Since these local controllers are of the multi-class type, the resulting ramp metering control actions are distinguished for different classes of vehicles. The results obtained by applying such a decentralised scheme are compared in the paper with those achieved by using a centralised control framework.